2020
DOI: 10.1093/ofid/ofaa131
|View full text |Cite
|
Sign up to set email alerts
|

The Time for Universal Masking of the Public for Coronavirus Disease 2019 Is Now

Abstract: In this perspective, we recommend universal masking of the US public during coronavirus disease 2019 due to the high contagiousness of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2), viral shedding of viable SARS-CoV-2 from asymptomatic individuals, and the likely contribution of masking to core distancing public health strategies for curbing transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 35 publications
1
29
0
1
Order By: Relevance
“…9 There are two likely reasons for the effectiveness of facial masks: The first-to prevent the spread of viral particles from asymptomatic individuals to others-has received a great deal of attention. 10,11 However, the second theory-that reducing the inoculum of virus to which a mask-wearer is exposed will result in milder disease [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] -has received less attention and is the focus of our perspective which compiles virologic, epidemiologic and ecologic evidence.…”
mentioning
confidence: 99%
“…9 There are two likely reasons for the effectiveness of facial masks: The first-to prevent the spread of viral particles from asymptomatic individuals to others-has received a great deal of attention. 10,11 However, the second theory-that reducing the inoculum of virus to which a mask-wearer is exposed will result in milder disease [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] -has received less attention and is the focus of our perspective which compiles virologic, epidemiologic and ecologic evidence.…”
mentioning
confidence: 99%
“…While the effectiveness of masks to prevent viral spread has been hotly debated, scientific studies have shown that even homemade masks can be effective at reducing virus spread 5,6 . Importantly, homemade masks were shown to primarily protect uninfected neighbors of infected individuals and were not as effective at protecting the wearer 7 .…”
Section: Impact Of Covid‐19 On Food Safetymentioning
confidence: 99%
“…After the Asian pandemic, the COVID-19 spread more rapidly in Europe and the US, but was gradually brought under control in Asia, due to the implementation of strict public protection measures in the region. For example, the Taiwanese Center for Disease Control requires people to wear masks in public places, including public transport, and that will be fined if they fail to comply, and until now Taiwan has maintained good control of the epidemic without a mandatory suspension of work and school [ 10 , 11 ]. Can masks play an effective role in the prevention and control of the spread of COVID-19?…”
Section: Introductionmentioning
confidence: 99%
“…Because they carry the virus, with a high concealment, it makes it more difficult to prevent and control the epidemic. The shedding of the virus from the asymptomatic carriers poses a great risk of transmission to the vulnerable population [ 10 , 28 ]. The results of the ‘Diamond Princess’ cruise liner incident showed that 18% of all infected individuals with SARS-CoV-2 in nasopharyngeal and oropharyngeal swabs did not show any symptoms [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation